(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
The life of motherhood and student hood is a challenging task. This study describes the barriers and strategies in coping up in the life of a student-mothers. The participants of the research consist of 12married students who are enrolled in Quirino State University Main Campus. This qualitative study utilized a phenomenological approach, which aimed to investigate the lived experiences of student-mothers. Individual interviews, focus group discussion and content/narrative analysis was utilized and purposeful sampling technique was used. Revealed in the study was the barriers in their studies which include situational and dispositional while strategies in coping up with their studies are time related strategies, attitudes/beliefs, and self-worth/efficacy. With these findings, the researcher recommends, Support systems could include intrusive advising, identification of an office to address problems or concerns, or the identification of an advocate or a problem solver. Use of curriculum (orientation to services) designed to inform student-mothers as to how they may successfully navigate, explore, and access university resources. Programs on mentoring, tutoring, study skills workshops, focus groups to assist the student-mothers.